Influences of combustion improver content and motionless time on the stability of two-phase emulsions. (2nd January 2018) - Lin, Cherng-Yuan; Tsai, Chang-Ting; Chen, Li-Wei
ABSTRACT: The heavy molecular bonds of liquid fuels can be broken with the assistance of a nitromethane fuel additive by virtue of its explosive and flammable properties to obtain greater heat release. Because of the immiscibility between nitromethane and petro-diesel, two-phase emulsions of nitromethane dispersed in the oil phase of a mixture of diesel and biodiesel were prepared. The experimental results show that microwave irradiation produced an emulsion with a larger number of dispersed nitromethane droplets in the continuous oil mixture, a smaller mean droplet size, and lower turbidity than magnetic stirring, and thus was a better method for preparation of the two-phase emulsion. The increase in the nitromethane weight fraction increased the number of dispersed nitromethane droplets and the emulsion turbidity. In addition, allowing the emulsion preparation to remain motionless for a longer period of time after either method resulted in an obvious reduction in the emulsification stability (ES).